Psychological Reactance Management via Nonlinear Dynamic Motivation in Classroom and Telecollaborative Second Language Learning Contexts - Akbar Bahari (Universitas Ahmad Dahlan, 2019)
Drawing on dynamic systems theory, FonF practice model and psychological reactance theory, the present study proposed reinforcing nonlinear dynamic motivation (NDM) as a facilitator to manage psychological reactance in three forms of incivility, dissent, and resistance among classroom and telecollaborative second language (L2) learners and teachers. Given the dynamicity and nonlinearity of motivation which differ from language to language and learner to learner, the current study aimed at exploring the possible impact of NDM on psychological reactance as a source of different behavioral problems in learning context. To find out whether NDM has the potential to prevent/minimize psychological reactance with regard to learner-teacher anxiety, frustration, and self-doubt a mixed methods study was conducted among 275 EFL learners. Implications of the study include the significance of NDM-oriented strategies at managing reactance in three forms of resistance, incivility, and dissent. Methodological triangulation of data from different participants and different contexts with regards to oppositional behavior indicated significant relationship between NDM and managing reactance among language teachers as well as language learners.